Enhanced Growth Performance Physiological and Biochemical Indexes of Trachinotus ovatus Fed With Marine Microalgae Aurantiochytrium sp. Rich in n-3 Polyunsaturated Fatty Acids - Li, Shuangfei; Wang, Boyu; Liu, Liangxu; Song, Yingjie; Lv, Chuhan; Zhu, Xingyu; Luo, Yanqing; Cheng, Christopher H. K.; Chen, Huapu; Yang, Xuewei; Li, Tao (Frontiers in Marine Science, 2021)
Aurantiochytrium sp. is a major source of n-3 polyunsaturated fatty acids (n-3 PUFAs), which are essential nutrients for marine fish. n-3 PUFAs have drawn increasing attention because of their great potential for improving the biological functions of fish. The growth performance and immune response of Trachinotus ovatus were studied by applying diets with various microalgae content from 1.00% to 11.00% for 8 weeks. The results showed that, with the addition of Aurantiochytrium sp., the survival rate, weight gain rate, and specific growth rate of fish increased by a maximum of 1.02, 1.16, and 1.08 times, respectively, indicating that the intake of marine microalgae Aurantiochytrium sp. was beneficial for fish growth. As the microalgae content increased, the feed utilization efficiency index feed conversion ratio decreased (maximum 15.00%) and feed efficiency increased (maximum 1.17 times), showing that the addition of Aurantiochytrium sp. contributed to the assimilation of fish feed. Furthermore, our results showed that as the addition of Aurantiochytrium sp. increased (from 1.00% to 11.00%), the glucose content increased in the blood (from 9.04% to 27.80%). Changes in the blood cell count of immune-related cells (white blood cells, lymphocytes, monocytes, neutrophils, and red blood cells) were also observed. These results indicated that microalgae rich in n-3 PUFAs could increase the number of immune cells, thus helping to improve fish immunity and disease resistance.